Study of fetomaternal outcomes in maternal jaundice at term pregnancy - Fatima, Kaneez; Hayat, Fayaz Khan; Chandra, Mukul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Jaundice in pregnancy, although uncommon, is associated with significant fetomaternal morbidity and mortality. Etiologies include viral hepatitis, intrahepatic cholestasis of pregnancy (ICP) and acute fatty liver of pregnancy (AFLP), each carrying unique risks. Methods: This prospective observational study included 30 term pregnant women with jaundice (serum bilirubin ≥2.5 mg/dl), conducted at F.H. Medical College, Agra (July 2023–June 2024). Demographic, clinical and laboratory data were collected and outcomes were analyzed. Results: Viral hepatitis was the most common etiology (50%), followed by ICP (30%) and AFLP (20%). Hepatic encephalopathy and coagulopathy were noted in 13.3% and 23.3% respectively. Cesarean delivery occurred in 40% of cases. NICU admission was needed in 33.3% and perinatal mortality was 3.3%. Conclusions: Maternal jaundice at term is a critical condition requiring early diagnosis and multidisciplinary care. The severe outcomes associated with AFLP and viral hepatitis underscore the need for timely intervention.